Research on the Application of the Neuhaus School in Modern Piano Performance and Education - Du, Jincong (International Journal of Multidisciplinary Research, 2026)
As one of the world’s most influential schools of piano playing, the Russian school, particularly the Neuhaus school, holds irreplaceable importance as its core representative. This article focuses on the practical application of the Neuhaus school in piano performance and teaching. Through literature review and interviews, the author analyzes the significant role the Neuhaus school has played in piano performance to date. Furthermore, the article analyzes existing problems in piano performance and teaching in China, concluding that teachers lack theoretical knowledge and practical experience, and performers over-interpret performances. To address these issues, the author offers feasible suggestions to promote the healthy development of piano performance and education.